Numerical Study of High Spectral Efficiency and High-Temperature Energy Harvesting Metamaterial Emitter to Improve Thermophotovoltaic Performance - Sifan Tamiru; Fekadu Tolessa; Birke Alemu; Solomon Tiruneh; Abebe Belay; Gurmu Alemu; T. Gurumurthi (International Journal of Photoenergy)
Design work was done on a broadband and wide-angle selective pyramid metamaterial emitter. COMSOL Multiphysics software was used to study the emitter, which was made of tungsten and aluminum nitride. The width of the unit cell and the tungsten ground thickness were fixed while other geometric parameters, such as the base length of the pyramid, the height of the pyramid, and the thickness of the dielectric, were tuned to produce the emitter’s desired broadband emission. A high average emissivity over 0.96 below the cutoff wavelength (0.1 μm-2.2 μm) was seen in the numerical simulation. The developed metamaterial emitter also had good emissivity across a broad range of incidence angles, from 0° to 60°, and was polarization independent. In addition, the planned emitter for the InGaAs cell has a better spectral efficiency than the blackbody other designed emitter. In general, the planned selective nanopyramid emitter was realized with 75% spectrum efficiency for InGaAs band gap energy (0.55 eV) at 1200 K, which was greater than blackbody and prior papers.